Buck-Converter Photovoltaic Simulator - Feri Yusivar; M. Y. Farabi; R. Suryadiningrat; W. W. Ananduta; Y. Syaifudin (Institute of Advanced Engineering and Science, 2011)
This paper presents a Photovoltaic Simulator Simulation using Buck Converter with analysis using bode diagram. A state space simulator model is derived to provide a detail non-linear model. The PV Static Model is modified by adding a low pass filter in order to avoid an algebraic loop problem and able to analyze easier. PV simulator is realized by controlling buck converter’s current using PI Controller with reference from PV model. Then the model is linearized which is used for analysis purpose. The system is analyzed using bode diagram for its output voltage against its inputs of solar irradiance and cell’s temperature. The Load, Proportional Gain Kp, and Integral Gain Ki are varied to observe their effects into the system stability. It is noticed that the limits of gain stability system are so high at all values of load and gains so the Buck-Converter Photovoltaic Simulator, which is proposed here, can be declared as a robust system.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.92